Pre-Service Teachers’ Opinion about Using Digital Storytelling as a Tool to Learn Speaking Skills - Endang Sulistianingsih; Januarius Mujiyanto; Abdurrachman Faridi; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2022)
Abstract. Many studies have discussed effective instructions for teaching speaking skills, but very few studies that explored students' preferences regarding the appropriate instruction for improving their speaking skills. This paper tries to fill the research gap by finding out the student's opinions on the use of digital storytelling for their speaking skills instruction. This study recruited 28 pre-service teachers to be participants. A qualitative approach was employed to answer the problems in this study. The findings were derived from analyzing the pre-service teacher’s opinions through observations and interviews. The findings revealed that most pre-service teachers feel satisfied with using digital storytelling to learn speaking skills. Moreover, those pre-service teachers presume that speaking was no longer boring activity, it became both fun and challenging and develop their digital literacy. The study suggests that the activities during creating a digital storytelling project should be well prepared.